1997
DOI: 10.1021/es970123s
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphate Ester Flame Retardants and Plasticizers in the Indoor Environment:  Analytical Methodology and Occurrence

Abstract: Nine organophosphate esters, which are commercially used as plasticizers and/or flame retardants, were identified and quantified in air samples from some common indoor work environments, i.e., an office building, a day care center, and three school buildings. One of the compounds was identified as tri(2-chloroethyl) phosphate, a substance that has been shown to be a neurotoxic and genotoxic agent. The concentration levels of this substance were found to be as high as 250 ng/m 3 . In order to examine whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
114
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(124 citation statements)
references
References 21 publications
8
114
2
Order By: Relevance
“…The result is comparable with Moller's study that a mean particulate percentage of 86 725% was detected for total atmospheric organophosphate compounds in the North Sea [30]. Also, in the study sampling indoor air at two different flow rates using a personal active sampler, 499% of all the organophosphates were distributed on the filters, with less than 1% found in the PUFs [7].…”
Section: Atmospheric Ope Concentrations By Active Samplersupporting
confidence: 86%
See 1 more Smart Citation
“…The result is comparable with Moller's study that a mean particulate percentage of 86 725% was detected for total atmospheric organophosphate compounds in the North Sea [30]. Also, in the study sampling indoor air at two different flow rates using a personal active sampler, 499% of all the organophosphates were distributed on the filters, with less than 1% found in the PUFs [7].…”
Section: Atmospheric Ope Concentrations By Active Samplersupporting
confidence: 86%
“…Nevertheless, increasing awareness has been focused on the chemicals due to their usage as alternative FRs for polybrominated diphenyl ethers (PBDEs) [5]. The global demands of OPEs are expected to increase and the resulting more production and emissions into the environment may cause reemerging concern [6,7]. An overview discussed the environmental levels of FRs in several monitoring studies [8], indicating that total OPE concentrations generally exceeded those of PBDEs in indoor air environment, and the human exposure potentials caused by OPE contamination appeared to be higher.…”
Section: Introductionmentioning
confidence: 99%
“…As most PFRs are added to and mixed with, rather than chemically bound to the materials (van der Veen and de Boer, 2012), leaching could occur throughout the lifetime (Marklund et al, 2003) of these products. Reports have indicated that PFRs were ubiquitous in various environmental media, such as water (Chung and Ding, 2009;Bacaloni et al, 2008), air (Carlsson et al, 1997;Saito et al, 2007), dust (He et al, 2015;Stapleton et al, 2009), sediment Ricking et al, 2003), soil (Mihajlovic et al, 2011), and biota samples (Kim et al, 2011;Sundkvist et al, 2010). Furthermore, some of the harmful effects of PFRs on human health cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental monitoring has demonstrated that TBEP is frequently found in indoor air, house dust, soil, snow, surface water, wastewater, wildlife and human milk (Bacaloni et al, 2007;Campone et al, 2010;Carlsson et al, 1997;Chen et al, 2012;Dodson et al, 2012;Kim et al, 2011;Mäkinen et al, 2009;Marklund et al, 2005;Mihajlović and Fries, 2012;Möller et al, 2012;Sundkvist et al, 2010). For example, in water samples from Albano lake in Italy, TBEP concentrations ranged from 10 to 127 ng/L (Bacaloni et al, 2007).…”
Section: Introductionmentioning
confidence: 99%